A Comparative Analysis of Potential Digital Evidence in WhatsApp Web-Based and Mobile-Based Application - Mohd Idris, Anis Safi; Ab Rahman, Nurul Hidayah (Applied Information Technology And Computer Science, 2022)
WhatsApp has become the most popular instant messaging (IM) application for users to send and receive messages through a web browser and smartphone. As it becomes more popular among users, the chance of digital crimes might happen. There is a lack of investigation to compare the digital artifacts acquired from WhatsApp web-based and WhatsApp mobile-based identified in the previous study. This study attempts to forensically analyze and compare the artifacts that can be recovered in browser and mobile devices using a timeline approach. The research methodology consists of preparation, acquisition, analysis and validation phases. The investigation was done through simulation activities, acquiring images, analyzing artifacts and documenting using forensic examination guidance. The findings were analyzed manually using DB Browser SQLite and WordPad, which examined differences in artifacts recovered from both WhatsApp apps. Future work should consider using several WhatsApp forensics techniques to achieve digital evidence accuracy and completeness.